Anionic Dye Adsorption from Aqueous Solutions by Chitosan Coated Luffa Fibers - Cherdphong Seedao; Tanawat Rachphirom; Methinee Phiromchoei; Witawat Jangiam (ASEAN Journal of Chemical Engineering, 2019)
Chitosan (CS) is biopolymer derived from deacetylation of chitin which can be found mainly in crustacean shells such as shrimp, crab, lobster etc. CS powder has been used to remove dye in many research. However, it was difficult to separate CS powder from aqueous solution. Considering the three-dimensional sponge natural structure of luffa fiber. it may address this issue by coating CS onto the surface of luffa fiber. This adsorbent was called chitosan coated luffa fiber (CS-LF). The aim of this studied is to investigate the potential of CS-LF to remove the anionic dye. Congo red is representative of anionic dye. Adsorption of anionic dye from aqueous solution using CS-LF was studied in a batch system. The effect of chitosan concentration coated on luffa fiber and initial anionic dye concentrations had been investigated on adsorption equilibrium and adsorption kinetic. An adsorption isotherm data were regularly analyzed using Langmuir and Freundlich isotherm models. While, adsorption kinetic were basically evaluated by pseudo-first-order, pseudo-second-order and intraparticle diffusion equation. The results showed that the adsorption isotherm fitted well by Langmuir isotherm model with maximum adsorption capacity 20.37 mg/g. The anionic dye adsorption kinetic of CS-LF were greatest described by pseudo-second-order equation and rate-controlling step of anionic dye adsorption process may be chemical reaction. Therefore, CS-LF is potential adsorbent as low-cost adsorbent to remove anionic dye from aqueous solution and could be simply separated from aqueous solutions after used. Finally, our study is firstly report in anionic dye adsorption using chitosan coated luffa fiber.